Total Plate Number Test at 0.5 McFarland Standard in Escherichia coli Culture - Bhakti, Tirta Setya; Porwanti, Ratna; Pribadi, Putik; Rahmawati, Dewi (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2023)
Estimation of the number of bacteria can be calculated quickly by comparing the turbidity of the test bacterial suspension against the McFarland standard. In the microbiology laboratory, McFarland standard of 0.5 is often used as reference. There are still few scientific references about the estimated enumeration of bacteria according to McFarland standards. The purpose of this study was to provide basic information on the estimated number of E.coli bacteria according to the McFarland standard of 0.5. The analytical method use ISO SNI 16649-2: 2001 about the enumeration E.coli using TBX Agar specific media with 10 replications to get a good average result. The result of E.coli enumeration with the 0,5 McFarland standard was 4.0 x 107 colonies/mL. Thus the approximate information on the bacteria enumeration could be done quickly.